Pengaruh Gaya Kepemimpinan Motivasi dan Pelatihan terhadap Produktivitas Kerja Salesman Kanvas - Johannes, Antonius (Jurnal Widya Manajemen & Akuntansi, 2002)
This study intends lo examine the effect of leadership styles, motivation, and training on canvas salesmen productivity in Artha Boga Cemerlang, Corp, East Java. The purpose of this research is to find empirical evidence about productivity of canvas salesmen. This study hopes to give contribution to corporation development on the increase of productivity of canvas salesmen. The data were collected by distributing questionnaires to 66 canvas salesmen located in Artha Boga Cemerlang Corp East Java as a chosen sample. The distributed questionnaires were all returned completely and were analyzed by using SPSS version 7.5, The sample was selected using quota sampling. The hypotheses were tested using multiple regression model and partial correlation. The result indicates that leadership styles, motivation, and training simultaneously and partially have a positive significant effect on productivity of canvas salesmen. So, the hypotheses developed in this study are supported. From the three independent variables, leadership styles have the strongest effect on productivity of canvas salesmen. It is hoped that research in the future will examine other variables that may influence productivity of canvas salesmen.